2008
DOI: 10.1007/s10620-008-0623-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Hepatic Stimulator Substance in Experimentally Induced Fibrosis and Cirrhosis in the Rat

Abstract: Liver fibrosis results from sustained wound healing response to chronic liver injury. Liver cirrhosis, the end stage of the fibrotic process, is characterized by disruption of the entire liver architecture and reduced hepatocyte regenerative ability. Hepatic stimulator substance (HSS) is a liver-specific growth factor triggering hepatocyte proliferation in vitro and in vivo. Previous studies have indicated the involvement of HSS in animal models of acute liver injury. The aim of the present study was to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Studies carried out in vivo [20] and in vitro models [4] reported the role of several cytokines produced by the hepatocyte in the activation of hepatic stellate cells [21]. More recently extensive evidence was provided on the events associated with the hepatic lipotoxicity [22] with the hepatocyte as the main target of the so called "lipoapoptosis" [23].…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in vivo [20] and in vitro models [4] reported the role of several cytokines produced by the hepatocyte in the activation of hepatic stellate cells [21]. More recently extensive evidence was provided on the events associated with the hepatic lipotoxicity [22] with the hepatocyte as the main target of the so called "lipoapoptosis" [23].…”
Section: Discussionmentioning
confidence: 99%
“…They had free access to food and water, were kept in an airconditioned room at 21°C with a 12/12-h light/dark cycle and handled humanely in accordance with European Union Dig Dis Sci (2010) 55:276-284 277 Directive 609/86 for care and use of laboratory animals. Induction of liver fibrosis was performed by administration of TAA in drinking water (300 mg/l) during a three-month period, as previously described [12,42]. The animals were sacrificed one, two, and three months from the onset of TAA administration.…”
Section: Fibrosis and Cirrhosis Inductionmentioning
confidence: 99%
“…In practice, administration of an HSS-bearing plasmid by hydrodynamic tail vein injection protects mice from hepatic failure, implying its potential role in clinical application. It has been demonstrated that alterations in HSS gene expression could be observed in relation to pathological states, such as acute liver failure (Li et al, 2011), liver cirrhosis (Gribilas et al, 2009), and hepatocellular carcinoma (Thasler et al, 2005;Dayoub et al, 2011). HSS seems to have additional clinical implications because exogenous HSS administration to rats with thioacetamide-induced liver fibrosis/cirrhosis is able to significantly decrease fibrosis and suppress the onset of cirrhosis (Gribilas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that alterations in HSS gene expression could be observed in relation to pathological states, such as acute liver failure (Li et al, 2011), liver cirrhosis (Gribilas et al, 2009), and hepatocellular carcinoma (Thasler et al, 2005;Dayoub et al, 2011). HSS seems to have additional clinical implications because exogenous HSS administration to rats with thioacetamide-induced liver fibrosis/cirrhosis is able to significantly decrease fibrosis and suppress the onset of cirrhosis (Gribilas et al, 2009). ALR is critically important for the survival of hepatocytes because of its association with the maintenance of mitochondrial stability (Thirunavukkarasu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%